Diffusion Restriction in the Optic Radiation of Term Neonates With Hypoxic-Ischemic Encephalopathy Demonstrated by Magnetic Resonance Imaging (MRI). (October 2021) - Hayakawa, Katsumi; Tanda, Koichi; Nishimura, Akira; Kinoshita, Daisuke; Kizaki, Zenro; Ohno, Koji
Objective: There has been no previous report of diffusion restriction in the optic radiation of term neonates with hypoxic-ischemic encephalopathy. Here, using diffusion-weighted magnetic resonance imaging (MRI), we assessed diffusion restriction in the optic radiation within the first 2 weeks of life and estimated signal changes and the apparent diffusion coefficient in the optic radiation and lateral geniculate body using T1-weighted MRI. Materials and Methods: Forty-five term neonates with hypoxic-ischemic encephalopathy underwent MRI twice during the first 2 weeks of life. Diffusion-weighted imaging and apparent diffusion coefficient were used to evaluate the presence of diffusion restriction in the optic radiation and lateral geniculate body. Apparent diffusion coefficient and T1 signal changes in the optic radiation and lateral geniculate body were also compared with those in 11 control neonates showing a normal pattern on MRI. Results: Diffusion restriction in the optic radiation was observed in 29% (13/45) of the hypoxic-ischemic encephalopathy neonates at a median age of 3.5 days (range: 1-9 days). The apparent diffusion coefficient in the optic radiation of affected neonates was significantly reduced in comparison with the controls. In all neonates with optic radiation involvement, increased T1 signal intensity was observed in the optic radiation in the second week, and was also evident in in lateral geniculate body in 8 of those neonates. Conclusion: Diffusion restriction in the optic radiation is not rare among term neonates with hypoxic-ischemic encephalopathy, being visualized by diffusion-weighted imaging in the first week of life and also high-intensity T1 signal changes in the second week. This diffusion restriction in the optic radiation might be due to transsynaptic neuronal degeneration.